2012
DOI: 10.1016/j.neuroimage.2011.09.029
|View full text |Cite
|
Sign up to set email alerts
|

BOLD responses in reward regions to hypothetical and imaginary monetary rewards

Abstract: Monetary rewards are uniquely human. Because money is easy to quantify and present visually, it is the reward of choice for most fMRI studies, even though it cannot be handed over to participants inside the scanner. A typical fMRI study requires hundreds of trials and thus small amounts of monetary rewards per trial (e.g. 5p) if all trials are to be treated equally. However, small payoffs can have detrimental effects on performance due to their limited buying power. Hypothetical monetary rewards can overcome t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 59 publications
(83 reference statements)
1
21
0
Order By: Relevance
“…Since monetary rewards were fictive, these conditions provide important criterion checks, confirming that participants were sensitive to differences in expected monetary pay-offs. Consistent with a previously demonstrated correspondence between real and fictive monetary rewards, in both behavioral choice and neural correlates789, a planned comparison revealed that participants’ choices were indeed in accordance with expected monetary rewards: the proportion of high- over zero-divergence choices was significantly greater in UBS than in UBO blocks, t ( 23 ) =  4 . 88 , p  <  0 .…”
Section: Resultssupporting
confidence: 80%
“…Since monetary rewards were fictive, these conditions provide important criterion checks, confirming that participants were sensitive to differences in expected monetary pay-offs. Consistent with a previously demonstrated correspondence between real and fictive monetary rewards, in both behavioral choice and neural correlates789, a planned comparison revealed that participants’ choices were indeed in accordance with expected monetary rewards: the proportion of high- over zero-divergence choices was significantly greater in UBS than in UBO blocks, t ( 23 ) =  4 . 88 , p  <  0 .…”
Section: Resultssupporting
confidence: 80%
“…Second, real and virtual rewards appear to be processed in a similar way. For instance, it has been shown that real and virtual reward induced similar behavioral responses (Bowman and Turnbull, 2003) and brain activation patterns (Miyapuram et al, 2012). Future work should further characterize smokers as slow and fast metabolizers using H3/cotinine ratios as this might influence the findings.…”
Section: Discussionmentioning
confidence: 99%
“…The mDG was identical to that in Study 1 except we instructed participants to imagine they had £100 to distribute among their network. The use of hypothetical rather than real money was motivated by the preferences of the school from which the sample was recruited and based on evidence that hypothetical money effectively motivates participant behavior (Miyapuram, Tobler, Gregorios-Pippas, & Schultz, 2012).…”
Section: Methodsmentioning
confidence: 99%